2017
DOI: 10.1190/int-2016-0011.1
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and pitfalls in surface-wave interpretation

Abstract: CitationSchuster GT, Li J, Lu K, Metwally A, AlTheyab A, et al. (2017) Opportunities and pitfalls in surface-wave interpretation. AbstractMany explorationists think of surface waves as the most damaging noise in land seismic data. Thus, much effort is spent in designing geophone arrays and filtering methods that attenuate these noisy events. It is now becoming apparent that surface waves can be a valuable ally in characterizing the near-surface geology. This review aims to find out how the interpreter can e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Yaede et al (2015) and Sowards et al (2018) have employed the MASW (multichannel analysis of surface waves; Park et al, 1999;Schuster et al, 2017) method in modified form to image the base of the LWP and underlying basalt in the Hawaiian Islands to depths of up to 70 m. Although standard P-wave reflection surveys are able to image relict igneous textures within LWPs (Sowards et al, 2018) it could be difficult to detect the gradational transition from saprolite to bedrock. Drilling is expensive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yaede et al (2015) and Sowards et al (2018) have employed the MASW (multichannel analysis of surface waves; Park et al, 1999;Schuster et al, 2017) method in modified form to image the base of the LWP and underlying basalt in the Hawaiian Islands to depths of up to 70 m. Although standard P-wave reflection surveys are able to image relict igneous textures within LWPs (Sowards et al, 2018) it could be difficult to detect the gradational transition from saprolite to bedrock. Drilling is expensive.…”
Section: Introductionmentioning
confidence: 99%
“…Targets of opportunity such as stream banks and road cuts may not universally expose the base of the LWP and outcrop may be obscured by dense tropical vegetation. Yaede et al (2015) and Sowards et al (2018) have employed the MASW (multichannel analysis of surface waves; Park et al, 1999;Schuster et al, 2017) method in modified form to image the base of the LWP and underlying basalt in the Hawaiian Islands to depths of up to 70 m. Although standard P-wave reflection surveys are able to image relict igneous textures within LWPs (Sowards et al, 2018) it could be difficult to detect the gradational transition from saprolite to bedrock. Yaede et al (2015) concluded that MASW works well and generally detects the base of the weathering front to within a few meters accuracy, where depths to bedrock were known from drillers logs, geologic logs, and measured section from outcrop.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 31(a) displays one of the five raw shot gathers used to generate the phase velocity dispersion curves. Figure 31(a) presents the unprocessed shot gathered with the refraction energy, while the refractions Schuster et al, 2017). Since we observe a mean phase velocity of approximately 1050 m/s at 11 Hz for the the large spread of P-wave solutions for the last layer, despite having an S-wave velocity of 1230 m/s and a depth of roughly 15 m for that layer, there is no conclusive evidence that the layer below 15 m is a basaltic layer.…”
Section: E M O N S T R At I O N O N F I E L D Datamentioning
confidence: 99%
“…Measurements of T were made using well‐established geophysical methods, including multi‐channel analysis of surface waves (MASW; Park et al, 1999, 2007; Schuster et al, 2017; Sowards et al, 2018; Yaede et al, 2015) and in particular horizontal‐to‐vertical spectral ratio (HVSR; Nakamura, 1989; Nelson & McBride, 2019; Nelson et al, 2020). These were systematically employed to estimate LWP thicknesses across substrates of differing age such as Kohala on Hawai'i Island (0.303 Ma), Molokai (1.32 Ma), Oahu (2.0 Ma) and Kauai (4.0 Ma) (Ozawa et al, 2005; Sherrod et al, 2007; Sowards et al, 2018).…”
Section: Introductionmentioning
confidence: 99%